Three dimensional arthrokinematic analysis of the late preparatory phase of handball throwing - Baeyens, J. P. J.; van Roy, P.; Clarijs, J.-P.; de Schepper, A. (1998)
INTRODUCTION: At full cocking, functional instability of the glenohumeral (GH) joint is commonly found in handball players. In the past, 2D radiography was used to examine the in vivo translation of the humeral head (HH) on the glenoid cavity (GC). Considering the restraint validity of 2D methods to estimate 3D motion, 3D intra-articular GH kinematical data were obtained on the late cocking phase of handball throwing, using fast helical CT scanning. METHODS: Based on the CT data, 3D bone reconstructions of 3 asymptomatic and 3 functionally unstable GH joints (1 internal impingement, 2 with minor anterior GH instability) in handball players were acquired from a position with the shoulder in 90° abduction and 90° external rotation, and from a position of full cocking assessed on an individual basis. Kinematic analysis was based on a least squares method and linked to the finite helical axis (FHA) concept. After virtual disarticulation, a local frame was embedded on the GC. Subsequently, the GH FHA parameters of direction, rotation and shift were decomposed on this local frame. The displacement of the center of curvature of the HH was related to the GC. Based on an analytic error propagation model, the estimates of the rotation angle, the direction vector and the shift showed highly accurate results. The estimate of the position vector was insufficient for a mathematical analysis and therefore obtained graphically in the finite plane of motion, perpendicularly situated on the FHA. Subsequently, GH contact areal displacement of the mating articular surfaces was analyzed in this finite plane of motion. RESULTS: Towards full cocking, the HH of the asymptomatic shoulders practically did not externally/internally rotate on the local GC frame. The internal impingement demonstrated an accentuated GH external rotation, attended by a dysfunction in scapular setting, with a normal posterior translation of the HH on the GC. Minor anterior GH instability showed a diminished posterior translation of the center of the HH on the GC, as well as an accentuated external rotation. GH contact areal displacement in the normal throwing shoulders and the test case with internal impingement revealed roll behavior. The test cases with minor anterior GH instability featured a pivot. CONCLUSIONS: This research demonstrated the use of helical CT data reconstruction of joint structures with the implementation of an FHA approach to study the 6 degrees of freedom of intra-articular motion assessing a local articular embedded frame and contact areal displacements. The study provided insight in the arthrokinematics of functional instability of the GH joint at late cocking.